2013
DOI: 10.4236/ajps.2013.47170
|View full text |Cite
|
Sign up to set email alerts
|

Persian Shallot (<i>Allium hirtifolium</i> Boiss) Extract Elevates Glucokinase (GCK) Activity and Gene Expression in Diabetic Rats

Abstract: Hepatic GCK is a key enzyme in glucose homeostasis and, as such, is a potential target for treatment strategies of diabetes. We investigated the effect of Persian shallot (Allium hirtifolium Boiss) hydroalchoholic extract on blood glucose level, plasma insulin level, GCK activity and its gene expression. Thirty two male rats were divided into 4 groups of 8, diabetic groups received 100 and 200 mg/kg Persian shallot extract, diabetic control and normal control received 0.9% saline for 30 days. Investigations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Hydroalcoholic extract of A. hirtifolium can also protect rat liver cells against the effects of oxidants in alloxan-induced diabetes and reduce the serum concentrations of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), and lactate dehydrogenase (LDH) [10,11]. e favorable result of the hydroalchoholic extract of A. hirtifolium on reducing the serum blood glucose levels, glucokinase activity, and gene expression has also been suggested by other researchers [12]. Nevertheless, in another study, it has been shown that A. hirtifolium extract could not decrease serum levels of apo-lipoproteins, AST, ALT, glucose, or insulin, while it could significantly reduce serum levels of triglyceride and cholesterol as well as atherosclerotic plaque thickness to media [13].…”
Section: Introductionmentioning
confidence: 95%
“…Hydroalcoholic extract of A. hirtifolium can also protect rat liver cells against the effects of oxidants in alloxan-induced diabetes and reduce the serum concentrations of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), and lactate dehydrogenase (LDH) [10,11]. e favorable result of the hydroalchoholic extract of A. hirtifolium on reducing the serum blood glucose levels, glucokinase activity, and gene expression has also been suggested by other researchers [12]. Nevertheless, in another study, it has been shown that A. hirtifolium extract could not decrease serum levels of apo-lipoproteins, AST, ALT, glucose, or insulin, while it could significantly reduce serum levels of triglyceride and cholesterol as well as atherosclerotic plaque thickness to media [13].…”
Section: Introductionmentioning
confidence: 95%
“…Mahmoodi et al ( 8 ) have shown that oral administration of hydroalcoholic extract of Allium hirtifolium markedly enhances the GCK mRNA expression in the rat liver and consequently decreases blood glucose. In our study, we used the ethyl acetate fraction of Allium hirtifolium , and a prominent hypoglycemic effect was reached through using much lower doses (5 mg/kg) compared to Mahmoodi’s study (100 and 200 mg/kg), indicating higher purification of the active ingredients and hence higher potency.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the results presented by Ravingerova et al ( 22 ) and Nemeth et al ( 23 ), who showed that 4- and 8-week diabetes significantly decreases baseline heart rate and coronary flow. Although the actual mechanisms are not completely understood, some possible factors that might be involved in the progression of cardiovascular malfunction in diabetic rats include decreased hepatic glucokinase and hexokinase activity, increased oxidative stress due to excessive production of oxygen free radicals, reduced antioxidant defense systems ( 8 , 24 , 25 ), decreased endothelial nitric oxide (NO) release or production, decreased reactivity of vascular smooth muscle to NO in diabetic animals, and increased production of superoxide anions ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disulphide and trisulphide compounds are the most important compounds existing in Allium genus species (Rose et al 2005). There are many reports indicating that the shallot has pharmaceutical effects such as regulation of immune system (Jafarian et al 2003), antioxidant (Leelarungrayub et al 2006), antitrichomonas (Taran et al 2006), anticancer (Azadi et al 2008), hypoglycemic (Hosseini-Zijoud et al 2012;Mahmoodi et al 2013) and hepatoprotective activity.…”
Section: Introductionmentioning
confidence: 99%